Molecular and immunophenotyping characteristics of non-APML, CD34 and HLA-DR negative acute myeloid leukaemia (HLA-DRneg non-APML) - Seman, Zainina; Mohd Tohit, Eusni Rahayu; Muthu Krishnan, Amy Amutha Amanda; Ho, Caroline Siew Ling (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2024)
Introduction: Non-APML, CD34 and HLA-DR negative (HLA-DRneg non-APML) differ from acute promyelocytic leukaemia (APML). Morphology and blast immunophenotype alone cannot differentiate between the two; molecular confirmation is necessary (1). Nucleophosmin 1 (NPM1) is mainly found in the earlier type, while the PML-RARA mutation is characteristic of APML. This study aimed to characterise HLA-DRneg non-APML and APML through im-munophenotyping, molecular findings and post-induction chemotherapy remission rate. Materials and methods: A cross-sectional study was conducted at HSAJB, involving all cases diagnosed as acute myeloid leukaemia (AML) for 3 years. The proportions of APML and HLA-DRneg non-APML and their immunophenotypes, molecular mutations and prognosis were compared. Results: A total of 182 AML cases were analysed. There was no statistically signifi-cant difference in immunophenotypes between the two types of AML. However, more APML cases were negative for CD11c and CD14 compared to HLA-DRneg non-APML cases. Only 69 samples had positive molecular mutations. Four cases of HLA-DRneg non-APML had NPM1 mutations; another four cases had NPM1 with FLT3 ITD mutations. HLA-DRneg non-APML cases with NPM1 mutations had a relatively higher post-induction haematological remission rate than HLA-DRneg non-APML NPM1 with FLT3 ITD mutations. Conclusion: A more extensive antibody panel in flow cytometry and a larger sample size may yield better results in distinguishing the two types of AML.